2009
DOI: 10.1111/j.1467-9280.2009.02471.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual Parsing After Recovery From Blindness

Abstract: How the visual system comes to bind diverse image regions into whole objects is not well understood. We recently had a unique opportunity to investigate this issue when we met three congenitally blind individuals in India. After providing them treatment, we studied the early stages of their visual skills. We found that prominent figural cues of grouping, such as good continuation and junction structure, were largely ineffective for image parsing. By contrast, motion cues were of profound significance in that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
119
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 33 publications
11
119
2
Order By: Relevance
“…been probed through studies of controlled-reared animals [54], newborn human infants [55] and older children with a delayed onset of pattern vision [56,57]. Converging findings from all these strands of research provide evidence that animals from insects to humans recognize objects primarily on the basis of their shapes, regardless of task demands [58].…”
Section: Recognizing the Shapes Of Visual Formsmentioning
confidence: 99%
“…been probed through studies of controlled-reared animals [54], newborn human infants [55] and older children with a delayed onset of pattern vision [56,57]. Converging findings from all these strands of research provide evidence that animals from insects to humans recognize objects primarily on the basis of their shapes, regardless of task demands [58].…”
Section: Recognizing the Shapes Of Visual Formsmentioning
confidence: 99%
“…Long-term studies on previously blind humans who gained their visual senses after successful surgeries clearly revealed (i) that visual recognition is learned, (ii) that observation of motion and transformation of foreground objects are important, and (iii) that labels are less important than previously expected, (cf . [25]). …”
Section: Segmented Frames Input Sequencesmentioning
confidence: 99%
“…Compared to still images, videos offer several advantages: (i) It is relatively easy to segment an object from the background using motion and observed temporal consistency, (ii) videos capture a higher variability of an object's appearance, and (iii) a small set of videos already provides a large number of training images. Moreover, there are rich and easily accessible sources for realistic video material such as YouTube or Vimeo, and it has been reported in literature [3,25,31] that learning from continuous image sequences is also biologically plausible. Humans tend to learn and categorize moving objects first, i.e., foreground vs. background, learn valid transformations, etc., and then gradually extract general knowledge that also allows for improving the recognition skills on stationary objects.…”
Section: Introductionmentioning
confidence: 99%
“…This traditional picture has been refined recently (Maurer et al, 2005;Ostrovsky et al, 2009). Some phenomena of early deprivation are explained by Hebbian competition -pruning of exuberant neural connections that are present in early infancy.…”
Section: Perception Of Form and The Three-dimensional World In Newly mentioning
confidence: 99%
“…Third, early deprivation affects both the ventral and the dorsal system of vision, and there is no obvious overall difference in plasticity between the two streams. Ostrovsky et al (2009) examined high-level form processing in three subjects shortly after recovery. They found that static cues for image parsing like good continuation and junction structure were ineffective.…”
Section: Perception Of Form and The Three-dimensional World In Newly mentioning
confidence: 99%